Dietary mineral and vitamin supplementation improved the reproduction, the haematology, and some circulating biochemical's of cyclic East-Bulgarian and Arabian mares. Issue 1 (1st January 2021) - Popova, Maya; Malinova, Radka; Nikolov, Vasil; Georgiev, Boyko; Taushanova, Paulina; Ivanova, Maria
Abstract: This study aimed to investigate the dietary mineral and vitamin supplementation on the hematological, the circulating biochemical parameters, and the reproductive performance of cyclic mares aged 4–12 years old. Purebred Arabian (PAB, n  = 8) and East-Bulgarian (EBB, n  = 12) breeds were equally divided into treated and control groups. The nutritional supplement was given orally (50 g daily/animal/day) for seven consecutive days and repeated for 4 consecutive months. All mares were examined daily with ultrasound from exhibiting oestrus signs till ovulation. Blood samples were collected with and without anticoagulant before supplementation, on Day 7 and Day 120 for the measurement of ALT, lactate dehydrogenase, bilirubin, calcium, phosphorus, and creatinine and to perform full blood picture. The nutritional supplement decreased lactate dehydrogenase ( p <  .05) and creatinine ( p <  .05). Compared to the PAB mares, control mares had one day shorter oestrous cycle length (20.2 ± 2.13 vs 21.0 ± 2.46 days), but the treated EBB mares had two days shorter oestrus cycle (20.00 ± 1.202 vs 22.00 ± 0.93 days). The oestrus phase of the treated mares was shorter ( p <  .001) than that of the control mares (3.63 ± 0.38 vs 5.50 ± 0.31 days). The diameter of the dominant follicle varied ( p <  .05) between the two breeds that was 38.25 ± 1.90 and 36.94 ± 1.70 mm for treated and control EBB but was 35.38 ± 1.41 and 34.89 ± 1.35 mm for treated and control PAB. In conclusion, the nutritional supplement had a good effect on the reproductive status, and on the blood parameters (hematological and biochemical) of the mares, but more research is necessary to recommend its use. Highlights: The addition of the nutritional supplementation to the mares from the East-Bulgarian breed lead to shorter oestrus. There was a tendency to shorten the sexual cycle (up to 2 days) and increase the size of the dominant follicles in mares receiving the supplement.